Student Evaluation of Faculty:Psychometric Validity of Court’s Views - Haskell, Robert E. (Education Policy Analysis Archives, 1997)
In two previous papers, it was noted that while a controversial history of research on the reliability and validity of student evaluation of faculty (SEF) exists, it has not been typically viewed as an infringement on academic freedom, promotion, reappointment, and tenure rights. As a consequence, legal aspects of SEF are neither readily apparent, nor available. Legal rulings, their implications and assumptions in relation to their accuracy and psychometric validity where SEF are integral to the denial of academic freedom, tenure, promotion, and reappointment are reviewed along with the legal principles of Disparate Treatment and Disparate Impact, and the scientific Precautionary Principle in policy decisions.